MEMBUMIKAN NILAI NILAI AKHLAQ DALAM KITAB AL-FIYAH IBNU MALIK DI PONDOK PESANTREN ROUDHLATUL MUTAALLIMIN AL AZIZIYAH II SEBANEH BANCARAN BANGKALAN - Afandi; Moh. Lutfi (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2021)
The word moral comes from Arabic which has become an uptake language. It is the plural form of Khuluqun which means "temperament, character, custom, and so on. While the notion of morals according to the term is the will of the human soul that gives rise to an action easily because of habit without requiring consideration of the mind first. Ibn Malik's book of alfiyah is an Arabic grammar, syntext, and morphology compiled by the famous scholars' Sheikh Jamaluddin muhammad Bin Abdullah Bin Malik Al Andalusi. This research has a focus on discussing the value of akhlaq value contained in the book of alfiyah ibn malik. This study was conducted at Pondok Pesantren Roudhlatul Muta'allimin Al Aziziyah II Sebaneh, Bancaran, Bangkalan using descriptive qualitative research, data sources produced through unstructured interviews, participant observations and documentation. The informant was the caretaker and Manager of Pondok Pesantren Roudhlatul Mutaallimin al-Aziziyah II Sebaneh Bancaran Bangkalan. The results of the study show that: contained in the book of Alfiyah Ibn Malik not only qoidhah gramatic Arabic but the beauty of language and beauty of stacking can absorb some knowledge by understanding the lafad lafad baitnya and by living the meaning of the express will arise the meaning of the meaning implied in it.